Capacity Building of Government Officials in the Implementation of Electronic-Based Government Systems - Abdi Susanto; Amirul Mustofa; Sedarmayanti Sedarmayanti; Dian Ferriswara (Dynamics Social : International Journal of Social Sciences and Communication, 2026)
This research aims to analyze the capacity building of government personnel in implementing the Electronic-Based Government System (SPBE) at the Department of Communication and Informatics of Gresik Regency, which plays a strategic role in digital governance. This study uses a qualitative approach focusing on capacity development strategies and constraints at individual and organizational levels. The findings show that capacity building is carried out through two main strategies: human resource development and organizational strengthening. In human resource development, the establishment and training of an internal assessor team serve as key instruments in supporting SPBE implementation. This team represents institutionalized capacity, enabling the organization to independently conduct monitoring, evaluation, and quality assurance processes in a sustainable manner. This approach reflects a long-term strategy to strengthen institutional independence and reduce reliance on external parties. In organizational strengthening, capacity building focuses on optimizing organizational structure, work systems, coordination mechanisms, and regulatory support, including standard operating procedures. However, several constraints were identified. At the individual level, there is an imbalance in technical competencies, especially in information technology skills. At the organizational level, the lack of optimal follow-up after training highlights the need for more integrated human resource planning. These findings indicate that capacity building in SPBE implementation requires a systemic, well-planned, and sustainable approach to achieve effective, adaptive, and responsive digital government governance in the public sector.